Turk Cardiology Association Completion Report: COVID-19 Pandemic and Things to Know About Cardiovascular Diseases (25 March 2020) - Aktoz, Meryem; Altay, Hakan; Aslanger, Emre; Atalar, Enver; Aytekin, Vedat; Baykan, Ahmet Oytun; Yildirimturk, Ozlem (Kare Publ, 2020)
[Abstract Not Available]
Keywords: Converting Enzyme 2; Myocardial-Infarction; Sars-Coronavirus; Heart-Failure; Dilated Cardiomyopathy; Functional Receptor; Natriuretic Peptide; Ace2 Expression; Cytokine Storm; Angiotensin